Rapid antiretroviral therapy initiation in the Botswana Combination Prevention Project: a quasi-experimental before and after study. Issue 8 (August 2020) - Lebelonyane, Refeletswe; Bachanas, Pamela; Block, Lisa; Ussery, Faith; Abrams, William; Roland, Michelle; Theu, Joe; Kapanda, Max; Matambo, Stembile; Lockman, Shahin; Gaolathe, Tendani; Makhema, Joseph; et al.
Summary: Background: Ensuring that individuals who are living with HIV rapidly initiate antiretroviral therapy (ART) is an essential step in meeting the 90-90-90 targets. We evaluated the feasibility and outcomes of rapid ART initiation in the Botswana Combination Prevention Project (BCPP). We aimed to establish whether simplified ART initiation with the offer of same-day treatment could increase uptake and reduce time from clinic linkage to treatment initiation, while maintaining rates of retention in care and viral suppression. Methods: We did a quasi-experimental before and after study with use of data from the BCPP. The BCPP was a community-randomised HIV-prevention trial done in 30 communities across Botswana from Oct 1, 2013, to June 30, 2018. Participants in the 15 intervention clusters, who were HIV-positive and not already taking ART were offered universal HIV-treatment and same-day ART with a dolutegravir-based regimen at first clinic visit. This rapid ART intervention was implemented mid-way through the trial on June 1, 2016, enabling us to determine the effect of rapid ART guidelines on time to ART initiation and rates of retention in care and viral suppression at 1 year in the BCPP intervention group. Findings: We assessed 1717 adults linked to study clinics before rapid ART introduction and 800 after rapid ART introduction. During the rapid ART period, 457 (57·1%, 95% CI 53·7–60·6) individuals initiated ART within 1 day of linkage, 589 (73·7%, 70·6–76·7) of 799 within 1 week, 678 (84·9%, 82·4–87·3) of 799 within 1 month, and 744 (93·5%, 91·6–95·1) of 796 within 1 year. Before the introduction of rapid ART, 163 (9·5%, 95% CI 8·2–11·0) individuals initiated ART within 1 day of linkage, 276 (16·1%, 14·4–17·9) within 1 week, 839 (48·9%, 46·5–51·3) within 1 month, and 1532 (89·2%, 87·7–90·6) within 1 year. 1 year after ART initiation, 1472 (90·5%, 87·4–92·8) of 1627 individuals who linked in the standard ART period were in care and had a viral load of less than 400 copies per mL, compared with 578 (91·6%, 88·1–94·1) of 631 in the rapid ART period (risk ratio 1·01, 95% CI 0·92–1·11). Interpretation: Our findings provide support for the WHO recommendations for rapid ART initiation, and add to the accumulating evidence showing the feasibility, acceptability, and safety of rapid ART initiation in low-income and middle-income country settings. Funding: US President's Emergency Plan for AIDS Relief.